2018
DOI: 10.1038/s41366-018-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity and insular networks: associations with food craving

Abstract: Accumulation of visceral adiposity is linked to disrupted functional connectivity within the mIns and rIns networks. Furthermore, the link between the mIns network and food craving is mediated by visceral fat. Findings suggest that visceral fat disrupts insula coding of bodily homeostatic signals, which may boost externally driven food cravings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…The present study also shows that in both groups, visual food cues elicited higher brain activation in a cluster of brain areas including the insula. This is in line with several previous studies [7,20,43]. Moreover, this finding validates the fMRI paradigm since mainly the posterior part of the insula receives ascending gustatory and gastrointestinal sensations while the anterior part conveys this information to other brain regions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also shows that in both groups, visual food cues elicited higher brain activation in a cluster of brain areas including the insula. This is in line with several previous studies [7,20,43]. Moreover, this finding validates the fMRI paradigm since mainly the posterior part of the insula receives ascending gustatory and gastrointestinal sensations while the anterior part conveys this information to other brain regions.…”
Section: Discussionsupporting
confidence: 92%
“…Very recently, a further study [43] aimed to test the link between visceral fat and the functional connectivity of the middle-dorsal insula and the rostral insula showed that higher visceral adiposity was associated with decreased connectivity between the middledorsal insula and a cluster involving the hypothalamus and the bed nucleus of the stria terminalis as well as between the rostral insula and the right amygdala. Decreased connectivity in this network was associated with greater food craving, a relation mediated by visceral adiposity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Further research should aim at ascertaining the putative mechanisms linking adiposity to overreaction to affective stimuli. Body fat has indeed been shown to modulate activity in other brain networks, such as those subserving homeostatic and reward signal processing 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Visceral obesity is closely associated with impaired metabolism and incidence of CKD. Computed tomography (CT) and magnetic resonance imaging (MRI) 7,15,16 provide accurate measurements of visceral obesity, but these imaging tests are expensive and may expose patients to radiation. Therefore, these techniques are rarely available in daily practice.…”
Section: Discussionmentioning
confidence: 99%